2016
DOI: 10.1093/jxb/erw418
|View full text |Cite
|
Sign up to set email alerts
|

Wortmannin-induced vacuole fusion enhances amyloplast dynamics in Arabidopsiszigzag1hypocotyls

Abstract: HighlightThe highly restricted movement of amyloplasts in graviperceptive cells of zig-1 hypocotyls is overcome by wortmannin treatment, suggesting a physical association between amyloplasts and the vacuole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…The meandering, wavy growth of vps38 roots (see Figure 3C ), along with the report that the PtdIn-3 kinase inhibitors LY294002 and wortmannin impair Arabidopsis gravitropism ( Joo et al, 2005 ; Jaillais et al, 2006 ; Alvarez et al, 2016 ), implicated VPS38 in gravity perception. As shown in Figure 10B , quantitation of this meander without reorienting the plants easily showed that vps38-1 and vps38-3 roots display a weaker gravity response as compared to WT or the VPS38-FLAG complementation lines.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The meandering, wavy growth of vps38 roots (see Figure 3C ), along with the report that the PtdIn-3 kinase inhibitors LY294002 and wortmannin impair Arabidopsis gravitropism ( Joo et al, 2005 ; Jaillais et al, 2006 ; Alvarez et al, 2016 ), implicated VPS38 in gravity perception. As shown in Figure 10B , quantitation of this meander without reorienting the plants easily showed that vps38-1 and vps38-3 roots display a weaker gravity response as compared to WT or the VPS38-FLAG complementation lines.…”
Section: Resultssupporting
confidence: 54%
“…In a similar fashion, mutations in the GRV2 protein important to vacuolar sorting also display dampened gravitropism ( Tamura et al, 2007 ; Silady et al, 2008 ). When connected with the prior observation that UNHINGED, which localizes to the TGN and prevacuolar compartments and regulates vesicle movements, also impacts auxin signaling ( Pahari et al, 2014 ) and that the zig-1 gravitropism mutant encoding the VTI11 SNARE protein is hypersensitive to wortmannin ( Alvarez et al, 2016 ), the links between PtdIn-3P, membrane trafficking, auxins, and root gravitropism become more obvious. Conversely, loss of VPS38 had only a slight effect on hypocotyl phototropism, but this dampened light response was complicated by the slowed hypocotyl elongation of the mutants.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is well recognized that a zigzag-shaped inflorescence stem results from the mutation of zig (zigzag)/sgr4, which encodes VPS10 interacting 11 (VTI11), a Qb-SNARE involved in vesicle transport between the trans-Golgi network and vacuole that causes abnormal gravitropism in Arabidopsis when mutated [8,10,11,38,39]. SNAREs play an important role in membrane fusion at the vacuole and are involved in the regulation of amyloplast sedimentation in response to gravity and in cell shape development [11,39]. ZIG can form a complex with other types of SNARE proteins, including SYP22/SGR3/VAM3, SYP5, and VAMP727, most likely at the prevacuolar compartment and vacuole [11,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…SNAREs play an important role in membrane fusion at the vacuole and are involved in the regulation of amyloplast sedimentation in response to gravity and in cell shape development [10,47]. ZIG can form a complex with other types of SNARE proteins, including SYP22/SGR3/VAM3, SYP5, and VAMP727, most likely at the prevacuolar compartment and vacuoles [10,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%